Determination of the bandwidth of the traffic lane of the circular part of the circular intersection with traffic light regulation and a cut-through central island - S. V. Ganzin; D. D. Silchenkov; Yu. A. Silchenkova (Интеллект. Инновации. Инвестиции, 2021)
The capacity of a road (street) is the maximum number of cars that a section of a road (street) can pass per unit of time in one or two directions in the considered road and weather and climatic conditions. In science, there are several approaches to determine the capacity: models based on dynamic models of traffic flow, the model of Birul A. K., Silyanov V. V., Tribunsky V. M., Khomyak Ya. V., Bilyatinsky A. A. and etc. In a practical way, they divide: theoretical, practical and maximum throughput. In the Russian Federation, there are a large number of guidelines for its determination. However, for a circular intersection with traffic light regulation and a cut-through central island (hereinafter referred to as KPSRPTSO), no such recommendations have been presented. After analyzing this traffic organization scheme, it was for the first time proposed to determine the capacity of the traffic lane of the KPSRPTSO half-ring. The purpose of the study is to improve the efficiency of the KPSRPTSO by determining the theoretical bandwidth of the traffic lane of a semi-ring of a traffic intersection. The article hypothesizes that the investigated theoretical throughput depends on two factors: the diameter of the traffic junction ring and the effective duration of regulation for the main road. To substantiate the adequacy of the calculations, the simulation method was used in the Aimsun software package (micromodeling). On the basis of data from field surveys of sections of the road network, a simulation model was created with a high degree of reliability, reflecting the current situation at regulated intersections, and the effectiveness of design solutions when organizing the KPSRPTSO was assessed. The relationship between the theoretical bandwidth of the KPSRPTSO half-ring and the diameter of the ring and the effective duration of regulation for the main road has been established. Comparison of the experimental data with the calculated values performed according to the recommendations of the methodological literature shows a discrepancy from 1% to 13%, which shows the qualitative convergence of the data. Further research involves the development of a methodology for calculating the parameters of the KPSRPTSO.